Botanical and management factors associated with Setaria pumila abundance implications for pasture management - Tozer, K.N.; James, T.K.; Cameron, C.A. (New Zealand Plant Protection, 2008)
Yellow bristle grass (YBG) causes significant production loss on dairy farms as it is unpalatable to stock and can reduce forage intake and milk production This weed is rapidly spreading in North Island dairy pastures and effective control strategies are needed Botanical surveying was undertaken in February 2008 on 12 dairy farms in Waikato to ascertain its presence in pastures in relation to key management factors YBG cover was negatively associated with Olsen P pH paspalum cover and postgrazing residual dry matter in January Stocking rate time since pasture renovation inclusion of a cropping phase prior to renovation sowing rate during renovation ryegrass undersowing after renovation and cover of ryegrass clovers other dicots annual grasses and amount of bare ground had no significant effect on YBG cover Results suggest that while improved soil fertility and increasing pasture competition will enhance YBG control YBG seeds can survive during pasture renovation leading to rapid reinfestation of pastures